The Evidentiary Legal Force of Auction Minutes Prepared By Class II Auction Officials in Disputes Over Voluntary Auction Objects - Agung Trilaksono; Petra Bunawan; Teddy Chandra (International Journal of Latin Notary, 2026)
This study examines the evidentiary legal force of the auction minutes (risalah lelang) prepared by Class II Auction Officials in voluntary auctions and the role of such minutes in legal disputes involving auction objects. The auction minutes constitute an official document that records the entire course and outcome of an auction and are therefore frequently invoked as evidence in auction-related disputes. The principal aim of this research is to assess whether the auction minutes can be relied upon as valid and authoritative evidence when challenged through litigation, particularly when a party claims to have been disadvantaged by the auction outcome. The research employs a normative juridical method, combining a statutory approach with case analysis. The findings indicate that auction minutes prepared by Class II Auction Officials possess significant legal force provided that the auction process complies with the applicable regulations. In practice, however, challenges arise, especially when third parties contest the procedure or outcome of the auction. The study recommends stricter supervision and clearer regulatory standards to ensure that the auction process is conducted in a fair and transparent manner.